Stereoselective construction of deoxy-cruciferane alkaloids by NHC-catalyzed intramolecular annulation of homoenolate with quinazolinone - Ahire, Milind M.; Pol, Mahesh D.; Kavale, Dattatry S; Gonnade, Rajesh G.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2019)
Chiral N-heterocyclic carbene (NHC)-catalyzed intramolecular [3 + 2] annulation of enals with an unactivated imine moiety of quinazolinone via formal homoenolate cycloaddition has been demonstrated. It is an excellent approach for stereoselective syntheses of deoxy-cruciferane alkaloids comprising a biologically important pyrroloindoline scaffold. Notably, this is the first report on the NHC-catalyzed asymmetric intramolecular homoenolate annulation with cyclic N-acyl amidine.